Rock aggregates plant: A preliminary feasibility study - Mendoza, Guadalupe Q. (Animo Repository, 1972)
The proposed rock aggregates plant will be located in Mariveles, Bataan. The project will involve a total capital requirement of 16 million pesos. The project calls for the establishment of and operation of a 320 ton-per-hour stationary rock crushing, screening and washing plant, or an estimated output of 816,000 cubic meters of processed aggregates per year operating for 300 days a year on a 16 hour/day operation, with an 85 percent efficiency rating. The study reveals the presence of current supply shortage of processed aggregates as well as sustained growth in the demand for processed aggregates. This sustained growth in the demand for processed aggregates will worsen the shortage situation unless new plants are established or existing plants expand their present capabilities. Other findings reveal a continued growth in the selling prices of processed aggregates, a condition favorable for the entry into the industry. An added advantage is the presence of a captive market which is estimated conservatively to absorb 30 percent of the plant's total output for the first three (3) years of operations and thereafter, captive market will be reduced by 30 percent every two (2) years. The captive market in this study refers to the other projects of the companies inside the Foreign Trade Zone and the anticipated development in the vicinity which will require the used of processed aggregates. The study further reveals substantial profitability, with a payback period of about 4 years and 7 months, and an average rate of return of 27 percent during the projected 10 year period.